Synthesis of Hollow CdS-TiO2 Microspheres with Enhanced Visible-Light Photocatalytic Activity - Yuning Huo; Jia Zhang; Xiaofang Chen; Hexing Li (International Journal of Photoenergy)
CdS-TiO2 composite photocatalyst in the shape of hollow microsphere was successfully synthesized via the hard-template preparation with polystyrene microspheres followed by ion-exchange approach. The hollow CdS-TiO2 microspheres significantly extended the light adsorption into visible light region, comparing to TiO2 microspheres. It led to much higher photocatalytic activities of hollow CdS-TiO2 microspheres than that of TiO2 during the photodegradation of rhodamine B under visible light irradiations. Furthermore, the well-remained hollow structure could achieve light multireflection within the interior cavities and the separation of photo-induced electrons and holes is efficient in CdS-TiO2, which were facilitated to improving the photoactivity.